Complexity of scientific evidence in environmental forensic investigations. Issue 4 (7th December 2015) - Spikmans, Val
Abstract : Purpose: – Environmental forensic investigations rely on the collection, analysis and interpretation of evidence from an environmental scene to assist in identifying the party responsible for the introduction of exogenous material. These investigations also try to elucidate if the environment and/or human health have been affected. The paper aims to discuss these issues. Design/methodology/approach: – Environmental forensic investigations are considered a sub-category of the forensic sciences. The potential scientific evidence is subjected to the same rigour as for other forensic science disciplines, including quality control, accreditation, chain of custody and evidence integrity. The manner in which evidence is analysed and interpreted is also similar. Even though strong similarities can be drawn between environmental forensic investigations and the general forensic sciences, some important differences need to be understood. Findings: – Environmental forensic investigations can be more complex than they first appear and identifying, analysing and interpreting scientific evidence is not always straightforward. It is crucial in the comprehension of the complexities of the environmental forensic discipline to understand the intricacies of the investigations, including the limited sample numbers, complex matrices, wide range of exogenous materials encountered, often large size of the scene, changes to the scene and, above all, the potential for degradation or transformation of evidence. In addition, scientific evidence is frequently used to gather intelligence rather than to provide knowledge that can be brought forward to determine guilt or innocence of an accused party. Originality/value: – This paper explores the complexities of the discipline and discusses the difficulties that are encountered during environmental investigations.